Facebook Use and Disordered Eating in College-Aged Women - Walker, Morgan (J Adolesc Health, 2015)
PURPOSE: Disordered eating behavior—dieting, laxative use, fasting, binge eating—is common in college-aged women (11–20%). A documented increase in the number of young women experiencing psychopathology has been blamed on the rise of engagement with social media sites such as Facebook. We predicted that college-aged women’s Facebook intensity (e.g., the amount of time spent on Facebook, number of Facebook friends, and integration of Facebook into daily life), online physical appearance comparison (i.e., comparing one’s appearance to others’ on social media) and online “fat talk” (i.e., talking negatively about one’s body) would be positively associated with their disordered eating behavior. METHODS: In an online survey, 128 college-aged women (81.3% Caucasian, 6.7% Asian, 9.0% African-American, and 3.0% Other) completed items, which measured their disordered eating, Facebook intensity, online physical appearance comparison, online fat talk, body mass index, depression, anxiety, perfectionism, impulsivity, and self-efficacy. RESULTS: In regression analyses, Facebook intensity, online physical appearance comparison, and online fat talk were significantly and uniquely associated with disordered eating and explained a large percentage of the variance in disordered eating (60%) in conjunction with covariates. However, greater Facebook intensity was associated with decreased disordered eating behavior whereas both online physical appearance comparison and online fat talk were associated with greater disordered eating. CONCLUSIONS: College-aged women who endorsed greater Facebook intensity were less likely to struggle with disordered eating when online physical appearance comparison was accounted for statistically. Facebook intensity may carry both risks and benefits for disordered eating.